Continuous tooth eruption adjacent to single‐implant restorations in the anterior maxilla: aetiology, mechanism and outcomes – A review of the literature. (9th March 2020) - Mijiritsky, Eitan; Badran, Maram; Kleinman, Shlomi; Manor, Yifat; Peleg, Oren
Abstract : Introduction: Dental trauma and congenital anodontia are common causes of anodontia in the anterior maxilla. The proposed restorative treatment constitutes a challenge for many dentists, particularly if it is a question of a young patient who has not yet completed skeletal and dental development. Current treatments for anterior maxillary anodontia include: fixed or removable partial dentures; orthodontic closure of interdental spaces; and dental implants. Dental implants do not move with the dento‐alveolar complex during the growth period of the maxilla. Therefore, many researchers maintain that implants should be postponed until after adolescence, in order to prevent complications, such as infra‐occlusion, that would require the replacement of the abutment and crown‐implant restoration, or even invasive treatments, such as the removal of the implant in the future. The objective of this literature review is to investigate the aetiology of the phenomenon, and outcome. Results: Continuous tooth eruption is not affected by age, so considerable changes may occur due to eruption of adjacent teeth. In addition, both women and men are affected by this phenomenon and, usually, there is no significant difference in the amount of growth between the short face and the long face. Conclusion: It can be concluded that continuous facial skeletal growth and teeth eruption are evident in the second and third decades. Where possible, it is advisable to delay placement of an anterior maxillary implant in the adolescent patient.